Bacterial cellulose-based electrochemical sensing platform: A smart material for miniaturized biosensors. (20th July 2020) - Gomes, Nathalia Oezau; Carrilho, Emanuel; Machado, Sergio Antonio Spinola; Sgobbi, Livia Florio
Abstract: Substantial scientific and technological progresses have prompted the development of point of care testing for health monitoring. However, most of the commercially available devices rely on invasive analysis based on blood samples. In this scenario, wearable sensing platforms have arisen as a promising non-invasive analytical tool. To fully exploit their capabilities, challenges must be overcome regarding good mechanical flexibility of wet devices upon bending and stretching movements, preserving the device integrity over the skin. Herein, we successfully developed an electrochemical biosensor made on bacterial cellulose (BC) substrate, and as a proof of concept, we demonstrated the detection of lactate in artificial sweat by immobilizing lactate oxidase (LOx) directly on BC substrate instead of on electrode surface. BC is a smart biocompatible material used as wound dressing with remarkable mechanical properties due to its nanometric fibers. The significant advantages of the proposed substrate for biosensors include biocompatibility, mass production of screen-printed electrodes (SPE) on BC, and superior mechanical resistance in comparison with vegetal cellulose even when hydrated. The electrochemical sensing platform was designed using a carbon-based working electrode modified with Prussian blue nanocubes, an efficient electron mediator for hydrogen peroxide, and LOx immobilized directly onto BC surface. The fabricated biosensor exhibited excellent amperometric response to lactate in the range of 1.0–24.0 mmol L −1 in artificial sweat with detection limit of 1.31 mmol L −1, and quantification limit of 4.38 mmol L −1 . The proposed sensing platform based on BC substrate paves the way to wearable devices with superior mechanical resistance and biocompatibility. Graphical abstract: Image 1 Highlights: Bacterial cellulose substrate provided superior mechanical resistance, even after several measurements in aqueous media. Bacterial cellulose allowed lactate oxidase immobilization directly onto its surface after chemical functionalization. A disposable paper-based biosensor detected lactate in artificial sweat using only 50 microliters of sample. Bacterial cellulose exhibited promising properties to fabricate wearable sensors in comparison to ordinary papers.